Optimization of the performance of a biomaterial-based wet scrubber system for enhancing pollutant gas absorption efficiency in environmentally friendly industrial applications - Hita, Muhammad Arga; Choiron, Miftahul (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
The rapid expansion of agro-industrial activities in Indonesia has led to a significant increase in exhaust gas emissions, including formaldehyde (HCHO), volatile organic compounds (VOCs), carbon dioxide (CO₂), and carbon monoxide (CO). These pollutants contribute to the formation of tropospheric ozone, acid rain, and greenhouse effects, which directly impact human health and ecosystems. Although wet scrubber technology is widely used to reduce such pollutants, conventional systems remain limited, particularly in capturing non-polar gases and micro-particles. This study developed a biomaterial-based wet scrubber system that integrates a mechanical approach (nozzle diameter variation) with a material approach (banana-stem biomaterial filter) to improve pollutant gas absorption efficiency. Four nozzle diameters (0.8, 0.5, 0.3, and 0.1 mm) and three biomaterial filter densities (50, 75, and 100 g/L) were tested for their performance in absorbing HCHO, VOCs, CO₂, and CO gases. The results demonstrated that the combination of a 0.3 mm nozzle and a 100 g/L banana-stem filter achieved the highest absorption efficiencies 87.5% for VOCs, 84.2% for HCHO, and 90.1% for CO₂. The decrease in water pH from 7.1 to 5.8 indicated enhanced dissolution of acidic gases, while the increase in TDS up to 1.350 mg/L reflected the accumulation of dissolved compounds due to absorption reactions. ANOVA analysis confirmed that both nozzle diameter and filter density significantly affected system efficiency (p < 0.05). This study highlights the potential of integrating biomaterial-based wet scrubber technology as an effective, economical, and sustainable solution for industrial air pollution control, supporting the transition toward green industrial practices in Indonesia.